The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1999
DOI: 10.1121/1.427152
|View full text |Cite
|
Sign up to set email alerts
|

The relative perceptual distinctiveness of initial and final consonants in CVC syllables

Abstract: Among the world's languages, syllable inventories allowing only initial consonants predominate over those allowing both initial and final consonants. Final consonants may be disfavored because they are less easy to identify and/or more difficult to produce than initial consonants. In this study, two perceptual confusion experiments were conducted in which subjects identified naturally produced consonant-vowel-consonant syllables in different frame sentences. Results indicated that initial consonants were signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
105
3
4

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(121 citation statements)
references
References 28 publications
9
105
3
4
Order By: Relevance
“…In natural materials, however, some degree of positional specificity of learning is expected, determined by the degree of acoustic similarity across positions. The less position-variable fricatives will likely result in less positional specificity in learning than will the more position-variable stop consonants (Redford & Diehl, 1999). The present findings therefore do not show whether prelexical representations are allophonic or phonemic.…”
Section: Discussioncontrasting
confidence: 34%
“…In natural materials, however, some degree of positional specificity of learning is expected, determined by the degree of acoustic similarity across positions. The less position-variable fricatives will likely result in less positional specificity in learning than will the more position-variable stop consonants (Redford & Diehl, 1999). The present findings therefore do not show whether prelexical representations are allophonic or phonemic.…”
Section: Discussioncontrasting
confidence: 34%
“…Redford & Diehl (1999) have shown that listeners to English CVC sequences make more errors identifying final consonants than initial ones. Discriminant analysis of acoustic measures confirmed a better performance for initial than for final consonants, 'suggesting that the perceptual advantage for initial consonants may be attributable to their greater acoustic distinctiveness ' (p. 1563).…”
Section: Phonetic Measures Of CV Vs Vc Syllable Structurementioning
confidence: 99%
“…Transitions are present only during the release of C2 into a following vowel, but not 6 during the release of C1, since there is no vowel following (for discussion, see Redford & Diehl 1999). Because the acoustic information for C1 is limited in this way, the degree to which the two consonants may overlap each other might be consequently restricted so as to preserve as much acoustic information as possible about each of the consonants.…”
Section: Effects Of Word Positionmentioning
confidence: 99%